An Analysis of the Generalizability and Stability of the Halo Effect During the COVID-19 Pandemic Outbreak - Gabrieli, Giulio; Lee, Albert; Setoh, Peipei; Esposito, Gianluca (Frontiers in Psychology, 2021)
The influence on the global evaluation of a person based on the perception of a single trait is a phenomenon widely investigated in social psychology. Widely regarded as Halo Effect, this phenomenon has been studied for more than a hundred years now, and findings such as the relationship between aesthetic perception and other personality traits —like competence and trustworthiness— have since been uncovered. Trustworthiness plays an especially crucial role in individuals’ social interactions. Despite the large body of literature published on the Halo Effect, and especially on the relationship between aesthetic appearance and perceived trustworthiness, little is known about the overall generalizability of the effect, as almost all of the studies have been conducted on adult participants from Western countries. Moreover, little is known about the stability of the effect over time, in the event of major destabilization, such as the outbreak of a pandemic. In this work, the cross-cultural generalizability of the Halo Effect is investigated before and during the first few months of the COVID-19 pandemic. An analysis of the generalizability and stability over time of the Halo Effect is presented. Participants (N = 380, N = 145 Asians, N = 235 Caucasians) have been asked to rate the aesthetic appearance and perceived trustworthiness of a set of human faces of different ages, gender, and ethnicity. Result of our analysis demonstrated that the Halo Effect (Aesthetic $×$ Trustworthiness) is influenced by the age of presented faces, but not by their gender or ethnicity. Moreover, our results show that the strength of the effect can be affected by external events and that the volatility is higher for adults' than children’s faces.